Role of the Janus kinase 2/signal transducers and activators of transcription 3 pathway in the protective effect of remote ischemia preconditioning against cerebral ischemia–reperfusion injury in rats. Issue 9 (12th June 2019) - Zhao, Yunlong; Xue, Yan; Liu, Zehan; Ren, Shuai; Guan, Xiangchen; Li, Ming; Zhao, Xin; Song, Yang; Ren, Xiaoping
Abstract : Remote ischemia preconditioning (RIPC) is a convenient and effective method for alleviating cerebral ischemia–reperfusion injury (CIRI). However, to date, the underlying mechanism has not been fully elucidated. The aim of this research was to explore the protective mechanism of RIPC on the brain after CIRI. Four groups of rats were included in this experiment: the sham group, the middle cerebral artery occlusion (MCAO) group, the RIPC group, and the AG490 group. As an inhibitor of Janus kinase 2 (JAK2), AG490 was used after MCAO in the AG490 group to explore the role of JAK2/signal transducers and activators of transcription 3 (STAT3) after CIRI. Brain tissue was collected for evaluation after 2 h of ischemia and 24 h of reperfusion. ELISA for interleukin (IL)-6, IL-1β and tumor necrosis factor-α, western blot for phosphorylated-JAK2 and phosphorylated-STAT3, the neurological severity score and Longa scoring system for neurological deficit evaluation, triphenyltetrazolium chloride staining for cerebral infarction, and terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling staining for apoptotic cells in the brain tissue were performed. Neurological function in the RIPC group was notably better than that in the MCAO group. There were smaller infarction sizes and fewer apoptotic cells in the ischemic area in the RIPC group than in the MCAO group. In the RIPC group, the expression levels of IL-1β, tumor necrosis factor-α, IL-6, and phosphorylated-JAK2 and phosphorylated-STAT3 were significantly lower than those in the MCAO group. The findings in the RIPC and AG490 groups were similar. The inflammatory response and apoptosis are two important processes involved in brain dysfunction after CIRI. The JAK2/STAT3 signaling pathway has an underlying relationship with these two processes. These findings suggest that RIPC can alleviate the damage to brain tissue by CIRI by regulating the JAK2/STAT3 signaling pathway negatively.